2014
DOI: 10.1136/jech-2014-204064
|View full text |Cite
|
Sign up to set email alerts
|

Physical and mental health outcomes following housing improvements: evidence from the GoWell study

Abstract: BackgroundExisting research points towards physical and mental health gains from housing improvements, but findings are inconsistent and often not statistically significant. The detailed characteristics and variability of housing improvement works are problematic and studies are often small, not experimental, with short follow-up times.MethodsA quasi-experimental design was used to assess the impact on physical health and mental health (using SF-12v2 Physical and Mental health component summary scales) of four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
58
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 23 publications
3
58
0
1
Order By: Relevance
“…[20][21][22] However, some housing policy has been implemented despite evidence from housing interventions suggesting small or unclear health effects. 23 Countries in temperate regions with fewer energy-efficient homes, including the UK, Greece, Portugal and Ireland, have more excess winter deaths, indicating that variations in winter mortality are caused by differences in indoor temperatures, health-care spending and socioeconomic circumstances. 24 Direct health impacts of cold housing and fuel poverty are thought to cause 33% and 40% of respiratory and cardiovascular diseases, respectively.…”
Section: Background/rationalementioning
confidence: 99%
See 4 more Smart Citations
“…[20][21][22] However, some housing policy has been implemented despite evidence from housing interventions suggesting small or unclear health effects. 23 Countries in temperate regions with fewer energy-efficient homes, including the UK, Greece, Portugal and Ireland, have more excess winter deaths, indicating that variations in winter mortality are caused by differences in indoor temperatures, health-care spending and socioeconomic circumstances. 24 Direct health impacts of cold housing and fuel poverty are thought to cause 33% and 40% of respiratory and cardiovascular diseases, respectively.…”
Section: Background/rationalementioning
confidence: 99%
“…23 A systematic review of the effects of improvements to housing found some evidence of health benefits following changes to thermal conditions, particularly when these interventions were targeted towards those with chronic respiratory conditions. 26,27 Evidence of health improvements not specifically targeted at vulnerable groups were less clear; authors noted that impacts measured for everyone in a housing improvement area may conceal health improvements for vulnerable population subgroups.…”
Section: Background/rationalementioning
confidence: 99%
See 3 more Smart Citations